PENGARUH MODEL DISCOVERY LEARNING DITINJAU DARI KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATA PELAJARAN MATEMATIKA KELAS V SD - Wahyu Windarti; Agustina Tyas Asri Hardini (JURNAL TEMATIK, 2020)
This research is a pre-experimental that aims to find out how to the implementation of Discovery Learning in terms of the students critical thinking skills in grade V Elementary math subjects . The research design used in this research is pretest-posttest design. The sample in the research were 30 students of grade V elementary school. There are three data collection techniques used in this research, namely test techniques that include pretests and pottest, of and documentation. The Analytical techniques used include the validity test and reliability test using the T-Test. The results of T-test analysis showed that the significance value is 0.00 < 0.05, then H0 rejected Ha accepted or could beconcluded that there was a influence on the implementation of Discovery Learning to the critical thinking ability of class V elementary students in mathematics. It is also supported from data that shows the acquisition of student grades after the Discovery Learning model is set up where 27 students have a value above 81 (90%) Compared to the model 's acquisition of the value of 69 (70%).